2010
DOI: 10.1177/0022429410369835
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Text Translation on Perceived Musical Tension in Debussy’s Noël des enfants qui n’ont plus de maisons

Abstract: The primary focus of the present study was to investigate the effect participants' (N = 100) knowledge of a text translation may have on their perceived musical tension while listening to a piece of choral music sung in another language. When examining the graphs that show the group mean responses of the participants, control (without text translation) versus experimental (with text translation), it is clear that there are many similarities between the groups. Any differences that may be attributable to an und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…With the right stimuli, such differences should be expressed in the activity of tonal tension rating changes at specific moments. Perhaps the impact of program notes and lyric translations (Hackworth & Fredrickson, 2010) or combinations of audio and video recordings might be better explored with measures of coordination. The added information may increase inter-response coherence without changing the contour of the average response.…”
Section: Discussionmentioning
confidence: 99%
“…With the right stimuli, such differences should be expressed in the activity of tonal tension rating changes at specific moments. Perhaps the impact of program notes and lyric translations (Hackworth & Fredrickson, 2010) or combinations of audio and video recordings might be better explored with measures of coordination. The added information may increase inter-response coherence without changing the contour of the average response.…”
Section: Discussionmentioning
confidence: 99%
“…When examining the present study through the lens of previous research, an interesting trend emerges. Two recent studies in the research literature revealed that text translation had no effect on participants' perceptions of musical tension (Hackworth & Fredrickson, 2010) and program notes actually had a detrimental effect on listeners' enjoyment of the music (Margulis, 2010). The present study seems to add to the growing body of research calling into question some of the previously held assumptions that program notes, text translations, and subtitles enhance the listening experience.…”
Section: Discussionmentioning
confidence: 99%
“…In either case, however, it appears that the importance of the text in vocal music is integral, and that the words are meant to accommodate the music and enhance the listening experience (Germano, 2010;Hackworth & Fredrickson, 2010;Peretz, Radeau, & Arguin, 2004;Skuggevik, 2010).…”
mentioning
confidence: 99%
“…Research utilizing the CRDI for perception of musical tension and individual variables has included effects of conductor (Fredrickson, 1994), performer use of rubato (Fredrickson & Johnson, 1996), age and/or sophistication of the listener (Fredrickson, 1997a), participation in rehearsal/performance (Fredrickson, 1999), listeners' musical proficiency (Fredrickson, 2000), dynamics (Misenhelter, 2001), performance medium (Fredrickson, 2001), jazz music (Fredrickson & Coggiola, 2003), music and text (Hackworth & Fredrickson, 2009), as well as artistic tension in dance (Frego, 1999).…”
mentioning
confidence: 99%